The larva of Dicterias Selys, 1853 (Odonata: Heliocharitidae [= Dicteriadidae]), and taxonomic and phylogenetic notes on Heliocharitidae - Fleck, Günther; Neiss, Ulisses G.; Hamada, Neusa (Zootaxa, 2012)
The larva of Dicterias Selys, 1853, a monotypic genus, is described and illustrated for the first time. It is morphologicallyvery close to the larva of Heliocharis Selys, 1853. The larvae of these two genera are compared, and a larval diagnosis forthe family is provided. The family Heliocharitidae (= Dicteriadidae) shares derived characters with some Calopterygoideaand is probably related to Calopterygidae. The larvae of Heliocharitidae are also amazingly similar to those of some Mega-podagrionidae, and long-legged Megapodragrionidae related to Megapodagrion could be related to the family Heliocharitidae and could represent a basal stem within the Calopterygoidea.